A study of profile of patients with organophosphorus compound poisoning at a teaching hospital - Vinod Govsavi; Vinayak E Shegokar; Sandeep M Bhelkar; Sudhir Tungikar (MRIMS Journal of Health Sciences, 2014)
Background: Organophosphorus compound poisoning forms an important public health problem especially in developing countries and rural population. Apart from its agricultural benefit its increasing use in agriculture, the farmer's and those involved in its manufacture are at increased risk. Objectives: To study the incidence of Organophosphorus compound poisoning and to study the profile of patients admitted with Organophosphorus compound poisoning. Methods: A hospital based cross sectional study was carried out from September 2002 to August 2003. A total of 200 patients were studied who were admitted to the hospital with Organophosphorus compound poisoning. Data was recorded in a pre designed questionnaire and proportions were used for analysis of the data. Results: Maximum cases of Organophosphorus compound poisoning (41%) were in the 21 – 30 years of age group. Both among males and females, maximum cases were married. It is seen that as the level of literacy increased the incidence of Organophosphorus poisoning is decreasing. Ingestion is the most common route of poisoning as seen in 99% of patients. Maximum i.e. 29.50% of poisoning cases were due to family conflict followed by marital conflict/disharmony. Most common Organophosphorus compound used for poisoning purpose was Roger i.e. Dimethoate in 43.5%. Conclusion: Thus we found that maximum cases were in the age group of 21 – 30 years, married group and among farmers and reported during June to October. Ingestion was the most common route of poisoning and family and marital conflicts were the most common reasons leading to poisoning. Among insecticides, Roger was the most common compound used for poisoning.